Hydrogen storage thermodynamic and dynamic properties of as-milled CeMgNi-based CeMg12-type alloys. (19th July 2019) - Zhang, Yanghuan; Shang, Hongwei; Yuan, Zeming; Li, Yaqin; Hou, Zhonghui; Qi, Yan; Dong, Xiaoping; Zhao, Dongliang
Abstract: Ni was chosen to partially substitute the Mg of alloys to investigate the effect on hydrogen storage dynamics of NdMg12 -type alloy. The amorphous and nanocrystalline alloys were synthesized by mechanical milling technology based on CeMg11 Ni +  x wt% Ni ( x  = 100, 200) alloys. This paper systematically narrates and investigates the influences of Ni content and milling duration on hydrogen storage performance. Sievert apparatus and differential scanning calorimetry (DSC) were utilized for investigating the de-/hydriding performances of samples. Both Arrhenius and Kissinger methods were utilized in this paper for estimating the dehydrogenation activation energy of hydrides, and found that enhancing Ni content can decrease the thermodynamic parameters (Δ H and Δ S ) of alloys slightly and improve the dehydriding dynamics significantly. Furthermore, the hydrogen storage property can be affected significantly by adjusting milling time. With varying milling time, the hydrogen storage capacities can reach the maximum values of 5.691 and 5.904 wt% for x  = 100 and 200 alloys separately. The hydrogen absorption saturation ratio ( R a (10)) at 573 K and 3 MPa also obtains maximum values with the variation of milling time, namely 90.17% and 99.32% for x  = 100 and 200 alloys separately. The hydrogen desorption ratio ( R d (20)) always increases with milling time increasing. To be specific, prolonging milling time from 5 to 60 h results in the increase of R d (20) at 593 K from 37.55% to 47.21% for x  = 100 alloy and 47.29%–61.70% for x  = 200 alloy. Highlights: CeMg11 Ni +  x wt% Ni ( x  = 100, 200) were prepared by mechanical milling. Enhancing Ni content can decrease the thermodynamic of the alloys slightly. The x  = 200 alloy has a better dehydriding dynamics than x  = 100 alloy. Prolong milling time can increase the R d (20) value of the alloys.